Synergistic Influence of Non-Thermal Plasma and Hydrogen Peroxide on Oxidative Desulfurization (ODS) of Model Fuel (Baghdad Science Journal, 2024)
Desulfurization is the process of removing the organic sulfur component from fuel oils. In this work, model fuel containing the sulfur compounds benzothiophene and dibenzothiophene was oxidized using plasma technique and plasma technique assisted by 30% hydrogen peroxide. Acetonitrile was used as a polar solvent in a liquid-liquid extraction stage that followed the oxidation reaction to remove the produced sulfones from the model fuel. The oxidation process was performed at operating conditions including the molar ratio of hydrogen peroxide to sulfur (5:1), temperature 50 ºC, air flow rate 75 ml/min, and voltage 11000 volts.   The oxidation reaction was done using a dielectric barrier discharge process for generating non-thermal plasma. The plasma technique and a combination of plasma with hydrogen peroxide together to oxidize BT and DBT. The results showed that both methods follow the pseudo-first-order reaction and that the removal efficiency is 93.78% per cent for plasma compared to the combination of plasma and hydrogen peroxide together, which reached 95.12%. Hydrogen peroxide (H2O2) in an aqueous solution is the most commonly used oxidant in oxidative desulfurization. However, the use of hydrogen peroxide creates organ wastewater, which must be collected and disposed of after the reaction, whereas ozone is a highly promising oxidant for oxidative desulfurization(ODS) since it does not produce wastewater and has a greater oxidation potential (2.8V) than hydrogen peroxide (1.7V). To put oxidative desulfurization with ozone into practice, establishing a more efficient desulfurization process with ozone is extremely desirable.